2001
DOI: 10.3171/jns.2001.94.3.0386
|View full text |Cite
|
Sign up to set email alerts
|

Use of intercostal nerves for neurotization of the musculocutaneous nerve in infants with birth-related brachial plexus palsy

Abstract: Neurotization of the MCN by surgically connecting ICNs is a safe, reliable, and effective procedure for reconstruction of the brachial plexus in patients suffering from birth-related palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
68
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 28 publications
(23 reference statements)
1
68
0
2
Order By: Relevance
“…Many publications in the medical literature detail successful means of treatment of patients of all ages with injuries to the brachial plexus, most commonly interposition nerve grafting, neurotization utilizing the intercostal nerves, and, more recently, the Oberlin procedure. 5,11,16,18,25,26,28,29,33,34,36,37 Experienced peripheral nerve surgeons are required to adapt on a case-by-case basis based on preoperative recovery patterns and intraoperative observations (for example, length of available nerves for direct neurotization and availability of proximal roots for grafting).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many publications in the medical literature detail successful means of treatment of patients of all ages with injuries to the brachial plexus, most commonly interposition nerve grafting, neurotization utilizing the intercostal nerves, and, more recently, the Oberlin procedure. 5,11,16,18,25,26,28,29,33,34,36,37 Experienced peripheral nerve surgeons are required to adapt on a case-by-case basis based on preoperative recovery patterns and intraoperative observations (for example, length of available nerves for direct neurotization and availability of proximal roots for grafting).…”
Section: Discussionmentioning
confidence: 99%
“…16,18,25,26,28,31,33 We report a 2-surgeon series at a single institution over 11 years in which MPN to MCN neurotization was performed in infants who had no return of elbow flexion following a birth-related injury.…”
mentioning
confidence: 99%
“…16,17,[22][23][24][25][26][27] The decision for surgery is generally taken in a time window ranging from 3 to 9 months, i.e. long before an end-stage of spontaneous recovery is reached.…”
Section: Assessment Of End-stagementioning
confidence: 99%
“…19,20 Methods of repair include nerve grafting after resection of the neuroma and nerve transfer in the case of root avulsion. 15,[21][22][23][24][25] Results achieved by these surgical approaches are claimed to be superior to the outcome in conservatively treated patients with equally severe lesions. 15,[26][27][28] However, this comparison relies on historical controls; 29 no randomized study has been performed.…”
mentioning
confidence: 99%
“…Subsequently, several authors have reported their experience with intercostal nerve transfer [4,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] . In order to restore maximum function of the arm, as many intercostal nerves as possible are harvested and transferred.…”
Section: Discussionmentioning
confidence: 99%